2021
DOI: 10.1051/0004-6361/202141067
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of recently discovered globular clusters in the Sagittarius dwarf spheroidal galaxy

Abstract: Context. Globular clusters (GCs) are important tools for rebuilding the accretion history of a galaxy. In particular, newly discovered GCs in the Sagittarius (Sgr) dwarf galaxy can be used as probes of the accretion event onto the Milky Way (MW). Aims. Our main aim is to characterize the GC system of the Sgr dwarf galaxy by measuring its main physical parameters. Methods. We built the optical and near-infrared color-magnitude diagrams for 21 new Sgr GCs using the VISTA Variables in the Via Lactea Extended Surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 135 publications
2
13
0
Order By: Relevance
“…More recently, the VVV/VVVX survey has revealed that the census of Galactic GCs is still not complete, and more than 300 new low-luminosity GC candidates have been identified in the VVV/VVVX bulge+disc area toward the inner galaxy (see e.g. Minniti et al 2020Minniti et al , 2021b, bulge region (Minniti et al 2017a(Minniti et al ,b, 2018bCamargo & Minniti 2019;Palma et al 2019;Garro et al 2021b;Obasi et al 2021), disc region (Garro et al 2020), the extension of the Hrid halo stream (Minniti et al 2021a), and the Sagittarius system (Minniti et al 2021c;Garro et al 2021a). A few of those candidates have been confirmed as true GCs (Contreras Ramos et al 2018;Gran et al 2019;Barbá et al 2019;Villanova et al 2019;Gran et al 2021a;Romero-Colmenares et al 2021;Dias et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the VVV/VVVX survey has revealed that the census of Galactic GCs is still not complete, and more than 300 new low-luminosity GC candidates have been identified in the VVV/VVVX bulge+disc area toward the inner galaxy (see e.g. Minniti et al 2020Minniti et al , 2021b, bulge region (Minniti et al 2017a(Minniti et al ,b, 2018bCamargo & Minniti 2019;Palma et al 2019;Garro et al 2021b;Obasi et al 2021), disc region (Garro et al 2020), the extension of the Hrid halo stream (Minniti et al 2021a), and the Sagittarius system (Minniti et al 2021c;Garro et al 2021a). A few of those candidates have been confirmed as true GCs (Contreras Ramos et al 2018;Gran et al 2019;Barbá et al 2019;Villanova et al 2019;Gran et al 2021a;Romero-Colmenares et al 2021;Dias et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (e.g. Keller et al 2010;Hyde et al 2015;Mucciarelli et al 2017;Hayes et al 2020;Garro et al 2021) have shown that a metallicity gradient is present both in the streams and in a small central region of the Sgr remnant, which is connected to the intricate chemo-dynamical evolution of this dwarf galaxy. The PIGS data is an excellent dataset to study the metallicity gradient in the core of the galaxy.…”
Section: Metallicity Gradientmentioning
confidence: 99%
“…Finally, the total luminosity in K s −band for each cluster is derived following the same approach of Garro et al (2021a). We first derive the absolute magnitude (M K s ) measuring the cluster total flux.…”
Section: Estimation Of Physical Parametersmentioning
confidence: 99%
“…Although Kharchenko et al (2016) have demonstrated that the larger contribution in luminosity arises from the brightest stars, since the first 10-12 members accumulate more than half of the integrated luminosity of the cluster, we are aware that the resulting M K s are a lower limit, because our photometry does not include fainter and lower mass stars. Therefore, in order to quantify the fraction of luminosity missed we adopt the same procedure of Garro et al (2021a), comparing the luminosity of our sample with those of known Galactic GCs. Once this luminosity fraction is obtained, we add this to the absolute magnitude and convert it into the absolute magnitude in V−band.…”
Section: Estimation Of Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation